Circular Economy Approach: Recycling Toner Waste in Cement-Based Construction Materials - Peralta Ring, Rocío (2024)
Based on a waste generated survey by companies in the area of the city of Bahia Blanca (Argentina), the possibility of incorporating part of them in a Portland cement matrix was examined. Among the waste is toner (TW), which is obtained from cartridges used in photocopiers, laser printers, and faxes. This paper aims to analyze the physical and mechanical properties of cement pastes and mortars using toner as a Portland cement replacement compared to a reference sample without toner. The mixes were made with 2.5, 5, 10, and 15 wt.% replacement of cement by toner, and it was measured the flow, normal consistency, setting time, calorimetry, and Frattini test in pastes and mechanical strengths in mortars employing standardized tests. Also, an analysis of the leachate in the curing water was carried out after 56 days to look for contaminating materials. The replacement of up to 5% cement with toner did not produce substantial alterations in the final setting time or mechanical properties. No heavy metals were found in the leachate, so TW can be immobilized in a cementitious matrix as it does not cause leaching above the established limits. Therefore, TW from a local industry can be used in construction materials and could contribute to a reduction of up to 14% of CO2 emissions with a cement replacement of 15% in cement-based materials.